Risk of postpolypectomy bleeding in patients taking direct oral anticoagulants or clopidogrel - Kim, Gwang-Un (Sci Rep, 2021)
The usage of direct oral anticoagulants (DOACs) to prevent and treat thromboembolic events is gradually increasing. We aimed to evaluate the outcomes of patients taking DOACs after polypectomy. We retrospectively reviewed 131 patients taking DOACs and 270 taking clopidogrel who underwent polypectomy between November 2010 and December 2017. The risk of delayed postpolypectomy bleeding (PPB) was evaluated and compared. A total of 989 polyps were removed (320 polyps in the DOAC and 669 polyps in the clopidogrel group). DOACs and clopidogrel were discontinued for 2.8 ± 1.7 days and 5.8 ± 2.5 days before polypectomy, respectively. DOACs and clopidogrel were restarted on 1.6 ± 2.9 days and 1.7 ± 1.1 days after polypectomy, respectively. According to per polyp analysis, delayed PPB rate was 1.6% in both groups (p = 0.924). Logistic regression analysis was performed after propensity score matching and revealed that DOACs did not increase the delayed PPB risk compared to clopidogrel (OR 0.929, 95% CI 0.436–1.975, p = 0.847). With the majority following the antithrombotic discontinuation guidelines, the incidence of delayed PPB was 3.1% in the patients taking DOACs. The delayed PPB risk was not greater in those taking DOACs than in those taking clopidogrel.